Urothelial carcinoma with sarcomatoid/osteosarcoma variant of the bladder: A case report - Murata, Masaki (SAGE Open Med Case Rep, 2020)
A 67-year-old man was diagnosed with non-muscle invasive bladder cancer and underwent transurethral resection of the lesions in August 2017. The pathological findings revealed high-grade urothelial carcinoma. The tumor relapsed as urothelial carcinoma with sarcomatoid/osteosarcoma variant with vascular invasion, and transurethral resection was performed in December 2017. He underwent laparoscopic radical cystoprostatectomy and orthotopic neobladder reconstruction using ileum in March 2018. The patient developed lung metastasis in July 2018. He underwent four courses of chemotherapy with doxorubicin and thoracoscopic left lower lobectomy of the lung in October 2018.